1996
DOI: 10.1016/0550-3213(96)00224-6
|View full text |Cite
|
Sign up to set email alerts
|

Gauge boson masses in the 3D, SU(2) gauge-Higgs model

Abstract: We study gauge boson propagators in the symmetric and symmetry broken phases of the 3-d, SU(2) gauge-Higgs model. Correlation functions for the gauge fields are calculated in Landau gauge. They are found to decay exponentially at large distances leading to a non-vanishing mass for the gauge bosons. We find that the W-boson screening mass drops in the symmetry broken phase when approaching the critical temperature. In the symmetric phase the screening mass stays small and is independent of the scalar-gauge coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
91
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 31 publications
16
91
2
Order By: Relevance
“…This is possible even for h close to 1, so that the system is far from the spinodal line. This case corresponds to weak first-order phase transitions, as can be verified by observing that the saddle-point action (6.17), the location of the true vacuum 20) and the difference in free-energy density between the minima ∆U m 3 6.21) go to zero in the limit m k f /λ k f → 0 for fixed h. This is in agreement with the discussion of fig. 25 in the previous subsection.…”
Section: Region Of Validity Of Homogeneous Nucleation Theorysupporting
confidence: 78%
See 2 more Smart Citations
“…This is possible even for h close to 1, so that the system is far from the spinodal line. This case corresponds to weak first-order phase transitions, as can be verified by observing that the saddle-point action (6.17), the location of the true vacuum 20) and the difference in free-energy density between the minima ∆U m 3 6.21) go to zero in the limit m k f /λ k f → 0 for fixed h. This is in agreement with the discussion of fig. 25 in the previous subsection.…”
Section: Region Of Validity Of Homogeneous Nucleation Theorysupporting
confidence: 78%
“…This concerns, in particular, the Lorentz symmetry or its Euclidean counterpart of four-dimensional rotations and Osterwalder-Schrader positivity [18]. In this line of thought the recent high precision numerical simulations of the high temperature electroweak interactions [19,20] can be considered as a fine example of a quantitative (theoretical) transition from microphysics to macrophysics, despite the presence of strong effective interactions and a large correlation length. They have confirmed that the high temperature first-order phase transition which would be present in the standard model with modified masses turns into a crossover for realistic masses, as has been suggested earlier by analytical methods [11,12,21,22].…”
Section: From Simplicity To Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by appealing to known d = 3 gauge dynamics, we can estimate the d = 4 coupling strength in terms of the renormalization constant Z. In d = 3 the coupling g 2 3 has dimensions of mass, and there is a unique [for given SU (N )] dynamically-determined ratio M/g 2 3 , which has been estimated by a number of authors [27,28,29,30,31,32,33,34,35,36,37]. Knowing only this ratio we can estimate the d = 4 QCD coupling α s (M 2 ), getting a value around 0.4Z.…”
Section: Introductionmentioning
confidence: 99%
“…The transition is of the first order at small Higgs masses, but it has been found to turn into a regular cross-over when m H > ∼ 75 GeV [1][2][3][4]. A second order transition appears at the endpoint of the first order transition line, and the macroscopic behaviour of the system is determined by the universal properties of the endpoint.…”
mentioning
confidence: 99%